1997
DOI: 10.1046/j.1365-313x.1997.12051103.x
|View full text |Cite
|
Sign up to set email alerts
|

Two TIP‐like genes encoding aquaporins are expressed in sunflower guard cells

Abstract: SummarySunTIP7 and SunTIP20 are closely related sunflower cDNAs showing a deduced amino acid sequence homologous to proteins of the tonoplast intrinsic protein (TIP) family. Their expression in Xenopus oocytes caused a marked increase in osmotic water permeability (demonstrating that they are water channels) which was sensitive to mercury. In leaves, in situ hybridization revealed that both SunTIP7 and SunTIP20 mRNA accumulated in the guard cells. The possible involvement of SunTIPs in stomatal movement was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(76 citation statements)
references
References 34 publications
1
73
0
2
Order By: Relevance
“…The theoretical possibility that hydraulic resistance of the guard cell membrane is temporarily increased (e.g. by regulation of aquaporins; Sarda et al, 1997;Huang et al, 2002), which would prevent quick equilibration, appears counterproductive because this would impede turgor loss of guard cells in a situation that demands stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical possibility that hydraulic resistance of the guard cell membrane is temporarily increased (e.g. by regulation of aquaporins; Sarda et al, 1997;Huang et al, 2002), which would prevent quick equilibration, appears counterproductive because this would impede turgor loss of guard cells in a situation that demands stomatal closure.…”
Section: Discussionmentioning
confidence: 99%
“…High expression levels of particular PIP and TIP aquaporins have been associated with: (i) high cell expansion rates Kaldenhoff et al 1995;Chaumont et al 1998;Weig & Eisenbarth 2000) (ii) cell differentiation (Kaldenhoff et al 1995); (iii) cells that exhibit large changes in volume, e.g. guard cells and pulvinar motor cells (Kaldenhoff et al 1995;Sarda et al 1997;Fleuratlessard et al 1997) (iv) high rates of water flow through cells (Barrieu, Chaumont & Chrispeels 1998;Kirch et al 2000;Otto & Kaldenhoff 2000;Frangne et al 2001) (v) the formation of a large central vacuole . For three TIP isoforms (γ α δ) there is an association with different types of vacuole (Jauh et al 1998;Jauh, Phillips & Rogers 1999).…”
Section: Patterns Of Mip Locationmentioning
confidence: 99%
“…Some members of the TIP-family also showed changed expression patterns when plants were exposed to water stress: rTIP in rice (Liu, Umeda & Uchimiya 1994), SunTIP7 in sunflower (Sarda et al 1997), and Bob-TIP26 in cauliflower (Barrieu et al 1999) were all expressed more. Conversely SunTIP18 in sunflower (Sarda et al 1999) and Cp-TIP in the resurrection plant (Mariaux et al 1998) and Mc-MIP F in Mesembryanthemum crystallinum (Kirch et al 2000) were down-regulated, when the plants lacked water.…”
Section: Effect Of Water Stress On the Expression Of Mip Genesmentioning
confidence: 99%
“…In the latter material, expression of most PIP genes was higher during the day than at night (Heinen et al, 2014). In sunflower (Helianthus annuus) guard cells, expression of vacuolar aquaporin SunTIP7 also showed diurnal variations, with an expression peak in phase with stomatal closure (Sarda et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has remained unclear whether the accompanying water flow across the guard cell plasma membrane and tonoplast can simply be mediated by the lipid phase of membranes or whether aquaporins, channel proteins that facilitate transmembrane water transport, are involved. In fact, information on aquaporin expression in guard cells has remained scarce (Sarda et al, 1997;Sun et al, 2001;Fraysse et al, 2005;Shope and Mott, 2006;Yang et al, 2006;Heinen et al, 2014). Plasma membrane intrinsic proteins (PIPs) represent the most abundant aquaporins in the plant plasma membrane (Santoni et al, 2003), and transcriptome analysis indicated expression of 8 and 12 PIP isoforms in stomata of Arabidopsis thaliana and stomatal complexes of maize (Zea mays), respectively (Leonhardt et al, 2004;Heinen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%